SUBALTERN IN LYNN NOTTAGE’S DRAMA SCRIPT, RUINED - Libranis, Marita; Fitria, Sari (ICoLLiTec (International Conference on Literature Linguistics and Teaching), 2023)
This study attempts to describe how the women are portrayed as subaltern, the discriminated group that cannot speak up to defend their right. This is proposed to reveal how the women characters are portrayed as subaltern and to uncover the impacts of subalternity toward the women. The writer uses the perspective of Subaltern by Gayatri Spivak (1988). This study applies a qualitative research method as the analysis is presented in the form of an essay. The result of the study shows that the women as subaltern are portrayed as a powerless and voiceless group of people. The second result is that subalternity brings negative impacts toward women, subversion and exploitation. They subvert the social norm by building a prostitution and exploiting the men’s sexuality to get her own advantages. The writer concludes that the discrimination toward the subaltern can cause a negative impact to the society, therefore, the reader should build awareness to decrease the discriminative action in the society